Ta'arruf As a philosophy of Muslim education : extending Abu Bakr Effendi's pragmatism - Waghid, Yusef (African Sun Press, 2020)
"In this book, Yusef Waghid constitutes his argument in defence of ta'arruf (associational knowing) as an expanded conception of ta'dib (good education). In the first part of the book he elucidates Abu Bakr Effendi's position on a Muslim educational philosophy which can be couched as rational, pragmatic and critical. As a backdrop to this, in the second part of the book, he argues for a notion of Muslim educational philosophy according to ta'arruf (associational knowing) on the basis that it enhances the notion of an autonomous self and its capabilities; summons different people to engage in deliberative encounters; and provokes the self to be reflectively open towards that which remains in becoming. This leads him to posit that ta'arruf (associational knowing) has the potential to cultivate humanity. His notion of ta'arruf extends practices of tarbiyyah (rearing), ta'lim (learning), and ta'dib (good education) associated with Muslim educational philosophy."--Publisher's description